2014
DOI: 10.1111/clr.12341
|View full text |Cite
|
Sign up to set email alerts
|

Novel hybrid drilling protocol: evaluation for the implant healing – thermal changes, crestal bone loss, and bone‐to‐implant contact

Abstract: Within the limitations of this study, the new hybrid protocol for the preparation of the implant bed without irrigation, increase the temperature similarly to the incremental conventional protocol, and requires twice the time for the completion of the drilling procedure in vitro. Crestal bone loss and bone-to-implant contact in the hybrid drilling protocol are comparable with the conventional drilling protocol and do not affect the osseointegration process in vivo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 57 publications
2
31
0
Order By: Relevance
“…A temperature elevation up to 38.9 • C for 4 min and 1-month follow-up [28] showed similar BIC values around treated implants (mean 43.1% SD 2.80) and untreated implants (45% SD 1.30).…”
Section: Bic Around Implants After Thermal Treatmentmentioning
confidence: 72%
“…A temperature elevation up to 38.9 • C for 4 min and 1-month follow-up [28] showed similar BIC values around treated implants (mean 43.1% SD 2.80) and untreated implants (45% SD 1.30).…”
Section: Bic Around Implants After Thermal Treatmentmentioning
confidence: 72%
“…Calvo-Guirado et al reported similar results. 34 They found that a simplified drilling sequence based on a 2-mm-diameter pilot drill at 100 rpm and a second final drilling with a 3.6-mmdiameter drill at 50 rpm without irrigation, increased the temperature similarly to the incremental conventional protocol and required twice the time for the completion of 3 . 7 Drilling was accomplished, depending on the respective surgical protocol, at a speed of between 500 and 2000 rpm and a load of 2 kg.…”
Section: Discussionmentioning
confidence: 99%
“…For most of the research concerning drills and drilling technique variations, the most commonly measured outcome concerns the heat generated at these sites as a function of different variables always referenced by a suitable control group (Calvo‐Guirado et al. ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has pointed that a region of necrotic bone surrounding the implant exists following surgery and that the extent of this region is influenced by drilling speed (Friberg et al 1995), design (Joos et al 2000;Huang et al 2007;Chung et al 2008;Gehrke et al 2015) and irrigation mode (or absence of irrigation). For most of the research concerning drills and drilling technique variations, the most commonly measured outcome concerns the heat generated at these sites as a function of different variables always referenced by a suitable control group (Calvo-Guirado et al 2015).…”
Section: Discussionmentioning
confidence: 99%